HALAL CUISINE IN MUSLIM-MINORITY URBAN PREFERENCE: CASE STUDY IN MANADO - Telsy Fratama Dewi Samad; Anggoro Sugeng; Talha Ayub; Taufani Taufani (Akademika : Jurnal Pemikiran Islam, 2022)
Halal cuisine becomes a captivating phenomenon not only among the Muslim regions but also in non-Muslim districts. This paper aims to reveal the phenomenon of halal cuisine in the Muslim minority region in Manado, North Sulawesi. This research used qualitative research with the study case approach. 5 Muslim merchants were interviewed to obtain some information according to this research. The result revealed the existence of Muslim merchants who are selling their halal cuisine in Manado as a Muslim minority religion and they are confident about the potency of halal cuisine development in Manado. The other findings show that the halal sign (logo) has been used by Muslim merchants to ensure the customers that the cuisine they promote is halal. Further, they disclose that the buyers come from Muslim customers and non-Muslim customers interested in buying their product. It can be concluded that even though Manado is known as a Muslim minority region, Muslim merchants possess a good position in Manado as merchants who are promoting their halal cuisine.